1987
DOI: 10.1007/bf00495002
|View full text |Cite
|
Sign up to set email alerts
|

Proteases in the human full-term placenta

Abstract: Aminopeptidase A, not yet defined aminopeptidases and endopeptidases, dipeptidyl peptidase I, II and IV, gamma-glutamyl transferase and oxytocinase were investigated in the normal human full-term placenta using qualitative (catalytic) cytochemistry, isoelectric focusing, immunocytochemistry and kinetic fluorometry. Aminopeptidase A could be visualized cytochemically in the smooth muscle cells of the chorionic plate, stem villi and basal plate blood vessels. Aminopeptidases were found in connective tissue fibre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1988
1988
1997
1997

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Reaction product measured in tissue homogenates, however, is developed by concomitant trophoblastic and fetal blood vessel and stroma/PVCS action. Reutter et al' reported on high binding affinities of DPP IV to extracellular matrix proteins, particularly to collagen I which [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] " 4 4 n=31 n=10 n=5 perivascular sheath. Our own observations (unpublished data) revealed a trend in decreased PVCS areas during me-eclammia.…”
Section: Discussionmentioning
confidence: 99%
“…Reaction product measured in tissue homogenates, however, is developed by concomitant trophoblastic and fetal blood vessel and stroma/PVCS action. Reutter et al' reported on high binding affinities of DPP IV to extracellular matrix proteins, particularly to collagen I which [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] " 4 4 n=31 n=10 n=5 perivascular sheath. Our own observations (unpublished data) revealed a trend in decreased PVCS areas during me-eclammia.…”
Section: Discussionmentioning
confidence: 99%
“…Our experience con firmed by other investigations confirms that fetal GGT activity shows little variation ac cording to gestational age in normal pregnan cies. Maternal GGT does not cross the placen tal barrier, and the placenta does not produce significant amounts of GGT [12]. Fetal serum and amniotic fluid GGT activity thus derives entirely from the fetus.…”
Section: Discussionmentioning
confidence: 99%
“…Undulin may interact with CD44 in smooth muscle cells. Elastin fibers are composed of elastin and oxytalan microfibrils, the latter of which bind to fibronectin and collagen type I cytochemistry, the enzyme was localized in smooth muscle cells and myofibroblast subpopulations of the PVCS (Feller et al 1985;Gossrau et al 1987;Graf et al 1994). This suggests, as possible functions of DPP IV, that it may act as an adhesion molecule to attach collagen type I to the plasma membrane and/or may be involved in the degradation of extracellular matrix together with metalloproteinases (MMPs; McDonald and Barrett 1986;Basbaum and Werb 1996).…”
Section: Discussionmentioning
confidence: 99%